Traces of the vocabulary in muhakemetü’l-lugateyn in turkish dialects of turkiye - Fatih; Neşe (Uluslararası Türk Lehçe Araştırmaları Dergisi)
One of the important works in terms of the history of Turkic language and Turkology is Muhakemetü’l-Lugateyn written by Ali Şir Nevâyî in the Chagatay field. The work is based on ‘the judgement of two languages’ and has very important language material in terms of vocabulary. In this work, Nevâyî compared Turkic and Persian and concluded that Turkic is superior to Persian with some of its features and showed the superiority of Turkic over Persian with some evidences. In doing so, he mentioned many linguistic materials such as verbs, kinship names, animal names, place names, riding teams, clothes, food and drink names. In this study, the vocabulary in Muhakemetü’l-Lugateyn was analyzed. The study analyzed 100 verbs that Nevâyî says are in Turkic but have no equivalent in Persian, along with other verbs in the work, kinship names, animal names, place names, riding teams, clothes, food and drink names and other names other names beyond these categories. The words in the work were analyzed separately as nouns and verbs in the analysis section, and the presence of these words in Turkish dialects, their current meanings, and the dialects in which they are used were determined. The information obtained was evaluated in the conclusion section